2010
DOI: 10.1175/2010waf2222418.1
|View full text |Cite
|
Sign up to set email alerts
|

Joint Diagnostic of the Surface Air Temperature in Southern South America and the Madden–Julian Oscillation

Abstract: The objective of this research is to explore the relationship between maximum and minimum temperatures, daily precipitation, and the Madden-Julian oscillation (MJO). It was found that the different phases of the MJO show a consistent signal on winter temperature variability and precipitation in southeastern South America. Additionally, this paper explores the spatial-temporal variations of mutual information and joint entropy between temperature and the MJO. A defined spatial pattern was observed with an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…In this sense, the present results provide an alternative perspective on the predictability of the intraseasonal component of summer SAT in Patagonia. This conclusion stands out, in agreement with the recent results of Alvarez et al [2015], and in spite of previous related findings, which showed that the mutual information between SAT and the MJO is highest not in Patagonia but in southeastern Brazil and northeastern Argentina, and features its maximum in autumn and winter and its minimum in summer [Naumann and Vargas, 2010]. Concerning the regional-and large-scale circulation patterns associated with the MJO signal in Eastern Patagonia, we found that positive (negative) SAT anomalies are linked to a midlevel anticyclonic (cyclonic) circulation anomaly centered over the southwest Atlantic and extending over southern South America, in agreement with previous work on regional summer SAT means [Jacques-Coper and Brönnimann, 2014].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this sense, the present results provide an alternative perspective on the predictability of the intraseasonal component of summer SAT in Patagonia. This conclusion stands out, in agreement with the recent results of Alvarez et al [2015], and in spite of previous related findings, which showed that the mutual information between SAT and the MJO is highest not in Patagonia but in southeastern Brazil and northeastern Argentina, and features its maximum in autumn and winter and its minimum in summer [Naumann and Vargas, 2010]. Concerning the regional-and large-scale circulation patterns associated with the MJO signal in Eastern Patagonia, we found that positive (negative) SAT anomalies are linked to a midlevel anticyclonic (cyclonic) circulation anomaly centered over the southwest Atlantic and extending over southern South America, in agreement with previous work on regional summer SAT means [Jacques-Coper and Brönnimann, 2014].…”
Section: Discussionsupporting
confidence: 92%
“…This conclusion stands out, in agreement with the recent results of Alvarez et al . [], and in spite of previous related findings, which showed that the mutual information between SAT and the MJO is highest not in Patagonia but in southeastern Brazil and northeastern Argentina, and features its maximum in autumn and winter and its minimum in summer [ Naumann and Vargas , ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Also, several MI metrics were developed to assist in predictor selection for hydroclimatic forecasting [ 48 , 49 ]. More importantly, MI was able to detect the presence of strong nonlinear associations of streamflow, rainfall, and global mean temperature with several large-scale climatic variables [ 31 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%